PEMAHAMAN MATEMATIKA MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING SISWA KELAS VIIC SMP NEGERI 2 MAESAN - MAHMIDAH MAHMIDAH (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2023)
The research aims to increase the activity and learning outcomes of the implementation of mathematics learning in subject matter of numbers by using a Contextual Teaching and Learning (CTL) approach. The learning process that has not been centered on students makes learning activities less and results in low student learning outcomes. The application Contextual Teaching and Learning (CTL) approach is expected to make learning more meaningful, because it will change the passive learning conditions to be active and creative so that students can gain their own knowledge about the implementation of mathematics learning in subject matter of numbers. The results showed 89,47% of students completed with an average value of  79.6. The application of Contextual Teaching and Learning (CTL) approach has been proven to be able to increase the activity and learning outcomes of the implementation of mathematics learning in subject matter of numbers in grade VII C students of Maesan 2 Junior High School in 2019/2020 Academic Year. ABSTRAKPenelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar matematika pada materi pelajaran bilangan dengan menggunakan pendekatan Contextual Teaching and Learning (CTL). Proses pembelajaran yang belum berpusat pada siswa membuat kegiatan belajar menjadi kurang dan berakibat pada rendahnya hasil belajar siswa. Penerapan pendekatan Contextual Teaching and Learning (CTL) diharapkan pembelajaran menjadi lebih bermakna, karena akan mengubah kondisi pembelajaran yang pasif menjadi aktif dan kreatif sehingga siswa dapat memperoleh pengetahuannya sendiri tentang materi bilangan. Hasil penelitian menunjukkan 89,47% siswa tuntas dengan nilai rata-rata 79,6. Penerapan pendekatan Contextual Teaching and Learning (CTL) terbukti mampu meningkatkan aktivitas dan hasil belajar matematika materi bilangan pada siswa kelas VII C SMP Maesan 2 Tahun Pelajaran 2019/2020.